The Integrated Post-Flood Health Services for Disaster-Affected Communities in Aceh - Hendra Kurniawan; Muhammad Dwi Hafizh Putra Setyo Raharjo; Muhammad Ammar Ibnu Syakir; Farah Narizki; Lyra Angelica (PT. Riset Mandiri Nusantara, 2026)
Flood disasters can severely disrupt access to essential healthcare services, particularly in vulnerable communities where health facilities and infrastructure are damaged. In November 2025, Tropical Cyclone Senyar caused extensive flooding in Pidie Jaya Regency, Aceh, resulting in disruption of healthcare access in Blang Awe Village. This community service program aimed to restore access to essential health services through an integrated post-disaster health intervention consisting of general health screening, maternal and child health (MCH) services, and medical circumcision. A participatory action approach was implemented from February 1–20, 2026, involving collaboration between the Faculty of Medicine, Universitas Syiah Kuala, Pidie Jaya District General Hospital, village authorities, and community health workers. The intervention included health screening, antenatal care (ANC), health education, and medical circumcision. Program outcomes were evaluated based on service achievement, community participation, stakeholder feedback, and perceived benefits. A total of 97 participants underwent health screening, identifying a high burden of non-communicable diseases, including hypertension (45%) and hypercholesterolemia (55.6%). ANC services were provided to 11 pregnant women with high-risk conditions identified, including suspected gestational diabetes and mild hypertension. Medical circumcision was successfully performed for eight school-aged children without complications. The program met its targets and received positive feedback from community stakeholders, indicating strong acceptance and perceived benefits. This integrated intervention successfully addressed healthcare gaps following flood-related disruption of health infrastructure by supporting continuity of essential services, improving early detection of health risks, and strengthening community resilience. Long-term sustainability requires strengthening local health worker capacity, referral systems, and integration into primary healthcare services.